Chronic intestinal pseudo-obstruction due to Strongyloides stercoralis. (2018) - Greenberg, Jenna; Greenberg, Joshua; Helmstetter, Nicholas
Abstract: We report a case of chronic intestinal pseudo-obstruction due to a generalized visceral autonomic neuropathy in an immune-competent patient infected with Strongyloides stercoralis . The patient had immigrated to the United States from Sierra Leone in childhood but had not returned for decades. His symptoms resolved with ivermectin treatment. Clinicians should have a high index of suspicion for strongyloidiasis in any patient with abdominal complaints and a history of travel to endemic areas, even if the travel history is remote.